Peran BUMDes Dalam Pemberdayaan Masyarakat (Studi Kasus BUMDes Manekan Desa Oefeto Kecamatan Amabi Oefeto Kabupaten Kupang) - Pah, Theny I. B. Kurniati; Lay, Marthina Raga; Therik, Jeny J. (Program Pasca Sarjana Universitas Garut, 2024)
This research tries to map the problem of the role of BUMDes Manekan which is located in Oefeto Village, Amabi Oefeto District, Kupang Regency. This research further highlights villages as a basis that must be considered in government management for welfare. Therefore, this research tries to analyze and describe the role of BUMDes Manekan in community empowerment in Oefeto Village, Amabi Oefeto District, Kupang Regency. The method used in this research is qualitative. Researchers try to look at the role of BUMDes Manekan, namely managing work units, managing resources within the business scope, preparing work plans, compiling reports. The role of BUMDes is more focused on the role of BUMDes in empowerment. So the research focus consists of fulfilling basic needs, access to public services, being able to participate actively, awareness of strengths and weaknesses in oneself and the environment, the ability to control oneself and one's environment. BUMDes Manekan has made most of its efforts to improve the community's economy, such as providing business capital, but is still hampered by stalled development. BUMDes management does not take into account community readiness. Capital is available but people cannot afford it because they are helpless.